Music as a Reflection of Female Struggles: Semiotic Analysis of ‘Girls Like Us’ - Evi Iryani (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2024)
This article examines the meaning in Zoe Wees' song "Girls Like Us" through semiotic analysis, highlighting the representation of issues faced by women in the current cultural and social context. In this research, the researcher uses a qualitative descriptive method to collect data from various sources such as books, e-books, journals, and internet news sources, and applies a quantitative algorithm using NVivo 14 Plus for word frequency analysis in the lyrics of "Girls Like Us." The analysis shows that the song “Girls Like Us” depicts the emotional and psychological struggles of women. Semiotic analysis of dominant words such as “know,” “like,” “girls,” and “hard” reveals themes of identity search, social challenges, and resilience. These words reflect Zoe's personal experiences while also representing the conditions faced by many young women worldwide. Through symbols and metaphors like “red lights in the darkness” and “heart in a cage,” Wees portrays feelings of loneliness, uncertainty, and the desire for recognition and acceptance. The message in these lyrics highlights the importance of understanding and empathy towards women's struggles, both in social and emotional contexts.